SMART BUILDING CONCEPT IN CREATIVE INDUSTRY DEVELOPEMENT DESIGN - Fauziah, Asyiqarizqi; Setiono, Arief Rakhman; Kusumadewi, Tarranita (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green TechnologyDO - 10.18860/icgt.v8i1.523, 2017)
The design of Creative Industries Developement Center is a developing creative industries which includes sixteen sub industry. Industrial development areas includes education, product development, creative industries community and marketing area of the creative industrial product. Smart building approach is applied to address related functions of the compound buildings with some users interacting and have different interests. Smart building method applies the principles of efficiency, effectiveness, user comfort, sustainability and systems enfironmental technologies. The principle of smart building analysed by theSmart Building Design Method of IBI (Intelligent Building Index) is expected to solve the problem by providing solutions in the form of integration between users. Related which gives comfort and convenience as well as integrated with the environment by implementing technology system.